Mandatory voice: Implementation of a district‐led student‐voice program in urban high schools. Issue 1 (21st October 2020) - Giraldo‐García, Regina J.; Voight, Adam; O'Malley, Meagan
Abstract: This qualitative case study explores how urban high schools implement a district‐initiated student‐voice program, referred to as Student Advisory Committees, intended to improve school climate. The study uses an implementation science framework to analyze interview data from principals and advisors in 22 urban high schools. An iterative, top–down thematic analytic procedure was used for analysis and interpretation of the data. The results suggest wide variation in how the program was implemented in terms of fidelity, dosage, quality, program reach, and adaptation, with contextual school factors—namely, principal and school characteristics—that help to explain this variation. In addition, the findings indicate that these contextual factors had a significant influence on how the school district implemented the student advisory committees. The authors discuss the implications for program implementation in the context of urban school districts and for school psychologists.